LOCAL WISDOM FUNCTIONALIZATION FOR REGIONAL LAW ENFORCEMENT IN FISHERIES MANAGEMENT - Josef M Monteiro; Jimmy Pello (Faculty of Law, Universitas Jenderal Soedirman, 2017)
Law enforcement for fisheries management violations in East Flores, East Nusa Tenggara province has not been effectively implemented. It is proven in recent years, violation’s cases of fisheries management is significantly high. This study examines how local wisdom values of indigenous society overcome the ineffective law enforcement for fisheries management violations. This paper employs normative juridical approach and was carried out by identifying and collecting customary law principles which govern fishermen’s attitude. The results show that law enforcement has not been effectively implemented to solve fisheries management violations in terms of the structure, substance and culture of law. To overcome this, it requires functionalization of local wisdom values that have been proven to alleviate marine resources damage by fishermen. Functionalization of local wisdom values is conducted by establishing a partnership between law enforcement and traditional authorities to institutionalize and integrate values system, cultural traditions, and customary penalty to have formal mechanisms of law enforcement.Keywords: local wisdom, law enforcement, fisheries